Peer Counselor as A Preventive Effort Against Early Marriage Using the Health Belief Model Approach - Damayanti, Eka; Astuti, Dhesi Ari (The Indonesian Institute of Science and Technology Research, 2024)
Early-age marriage presents a significant challenge in many developing countries, including Indonesia. Marriages occurring before the age of 18 often lead to adverse outcomes for adolescents, including pregnancy and childbirth complications that elevate maternal and infant mortality rates. Additionally, early marriage commonly disrupts adolescent education, limiting future employment opportunities. Effective preventive strategies, such as the